The effects of received social support on posttraumatic stress symptoms and social adjustment of New Zealand and Philippine emergency responders : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Wellington, New Zealand - Guilaran, Johnrev Barello (Massey University, 2019)
Emergency response work is associated with a wide range of psychological outcomes. One of the most commonly observed psychological consequences is posttraumatic stress symptoms (PTSS). In addition, traumatic exposure of these types are also seen to affect social adjustment, which may take the form of changes in satisfaction with social relationships and performance of social and occupational roles. In these highly stressful conditions, social support, behaviours and social interactions that provide actual assistance and embed people in loving and caring social networks (Hobfoll & Stokes, 1988), has been shown to be associated with favourable consequences. This research was conducted to test the effects of social support on PTSS and social adjustment in emergency responders – those who are mandated to protect and preserve life, property, and the environment (Prati & Pietrantoni, 2010) in the aftermath of emergencies and disasters. This thesis specifically focusses on received social support, which is the situational-environmental facet of social support. The first two manuscripts are meta-analyses on the associations of social support on psychological outcomes, to chart the topography of research in the area. Manuscript One is a systematic review and meta-analysis on the associations of social support on various psychological outcomes in emergency responders working in disasters. Manuscript Two is a meta-analysis on the influence of social support on posttraumatic stress symptoms in emergency responders, in general. In both meta-analyses, differential effects of social support were found, but there was a domination of studies on perceived social support and a scarcity of literature on received social support. Manuscripts Three through Five, which cover the results, then focussed on the association of received social support in 223 emergency responders from New Zealand (n = 195) and the Philippines (n = 28). Manuscript Three tested the main and moderating effects of received social support on PTSS while Manuscript Four tested its effect on social adjustment. For both studies, the effects of the different sources (i.e., family, peers, supervisor) and forms (i.e., emotional, tangible, informational) of received social support were also tested. Furthermore, to understand the protective assistance process between received and perceived social support, Manuscript Five tested the mediating effects of social support effectiveness and negative consequences on the relationship between received and perceived social support. The results of these studies highlight three key points. First, received social support is consistently shown to have main effects on PTSS and social adjustment. Second, reverse buffering effects were observed only in received supervisor support on PTSS. Third, support effectiveness and negative consequences do not mediate the link between received and perceived support in emergency responders. These findings suggest the limits of the effectiveness of social support on psychological outcomes, but at the same time, also suggest the potential of this naturally-occurring intervention element to enhance positive outcomes.
Listed in 2019 Dean's List of Exceptional Theses
The questionnaires in Appendix E: Questionnaire are subject to copyright and have been removed from the thesis.
Keywords: Post-traumatic stress disorder; Patients; Rehabilitation; First responders; Job stress; New Zealand; Philippines; Social networks; Psychological aspects; Adjustment (Psychology); Dean's List of Exceptional Theses